Analysis of speed control of DC motor (compound motor) using MATLAB (Simulink) and interface with graphical user interface (GUI) / Mohammad Bazli Mohd Azman - Mohd Azman, Mohammad Bazli (2010)
This paper presents the methods of speed control of a DC machine by simulation using MATLAB/SIMULINK. The simulation model will enhance a better understanding of how the actual machines work. The three methods to control speed are armature voltage control, armature resistance control and field control. There are several types of DC motor and compound DC motor was used in this analysis to verify the motor speed by using three methods above. The simulation results using MATLAB showed that the speed will change accordingly when the different type of speed control method has been applied. The evaluation of the output has been carried out by software simulation using MATLAB in the SIMULINK and displayed by using graphical user interface (GUI).